An assessment of the extent of empowerment through community participation : a Kwazulu-Natal rural development comparison - Gumbi, Themba Aaron Philemon (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2001.